Health equity monitoring is essential in public health: lessons from Mozambique - Llop-Gironés, Alba; Cash-Gibson, Lucinda; Chicumbe, Sergio; Alvarez, Francesc; Zahinos, Ivan; Mazive, Elisio; Benach, Joan (Globalization and Health, 2019)
Background: Countries must be able to describe and monitor their populations health and well-being needs in an attempt to understand and address them. The Sustainable Development Goals (SDGs) have re-emphasized the need to invest in comprehensive health information systems to monitor progress towards health equity; however, knowledge on the capacity of health information systems to be able do this, particularly in low-income countries, remains very limited. As a case study, we aimed to evaluate the current capacity of the national health information systems in Mozambique, and the available indicators to monitor health inequalities, in line with SDG 3 (Good Health and Well Being for All at All Ages). Methods: A data source mapping of the health information system in Mozambique was conducted. We followed the World Health Organization’s methodology of assessing data sources to evaluate the information available for every equity stratifier using a three-point scale: 1 - information is available, 2 - need for more information, and 3 an information gap. Also, for each indicator we estimated the national average inequality score. Results: Eight data sources contain health information to measure and monitor progress towards health equity in line with the 27 SDG3 indicators. Seven indicators bear information with nationally funded data sources, ten with data sources externally funded, and ten indicators either lack information or it does not applicable for the matter of the study. None of the 27 indicators associated with SDG3 can be fully disaggregated by equity stratifiers; they either lack some information (15 indicators) or do not have information at all (nine indicators). The indicators that contain more information are related to maternal and child health. Conclusions: There are important information gaps in Mozambique’s current national health information system which prevents it from being able to comprehensively measure and monitor health equity. Comprehensive national health information systems are an essential public health need. Significant policy and political challenges must also be addressed to ensure effective interventions and action towards health equity in the country.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; Health PEA; L - english / inglês; gender / género; health - health information systems / saúde - sistema de informação de saúde; health - maternal and child / saúde - materno-infantil; health - social determinants of health / saúde - determinantes sociais da saúde; health / saúde

A study of the actual and potential usage of information and communication technology at district and provincial levels in Mozambique with a focus on the health sector - Braa, Jørn; Macome, Esselina; Mavimbe, João Carlos; Nhampossa, José Leopoldo; da Costa, João Leopoldo; José, Bonifacio; Manave, Aurélia; Sitói, António (The Electronic Journal of Information Systems in Developing Countries, 2001)
This article presents results from a study on the use and appropriation of information and communication technologies (ICT) in Mozambique with a focus on the health sector. The three provinces of Gaza, Inhambane and Niassa were surveyed and two questionnaires addressing 1) computer users and their ability to manage ICT, and 2) health workers and their handling of health information, were used. Based on this study appropriate strategies for developing an ICT-infrastructure with the needs of the health sector as points of departure are discussed. The study is born out of a program to strengthen and further develop the health information and management systems at district and provincial levels as part of a process to support decentralisation of the health system in Mozambique. The study shows that computers and Internet are rapidly being spread to the provincial capitals and major districts in Mozambique. A main problem identified is the lack of ICT-skills and education and poorly developed infrastructure and networks of support. There are very few formal ICT companies providing hardware, and even less, software support. Maintenance and learning about ICT are to a large extent going on within informal networks of computer users in the provinces. A main finding in this study is that development of ICT capacity and information systems at district and provincial levels in Mozambique needs to be an integrated effort across sectors. A district health information system cannot be developed in a void. A general recommendation is to develop educational programmes ranging from training of ICT entrepreneurs and health workers and managers, to Masters and PhD programmes in ICT and health information systems. A specific recommendation related to health information systems development is to focus on the district level and to develop a strategy which encompasses and integrates all districts, both the advanced districts with computers and the majority of the districts where there are no computers.
Keywords: *indexed; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; health - health information systems / saúde - sistema de informação de saúde; health / saúde